Idk why but I need an image answer for this...
8.25
x6.75

Answers

Answer 1
Answer:

Answer: 55.6875

Step-by-step explanation:

Answer 2
Answer:

Answer:

8.25

x6.75

Step-by-step explanation:

55.6875


Related Questions

Pleaae help it would mean so much to me,ill even give you five stars​
Tomas learned that the product of the polynomials (a b)(a2 – ab b2) was a special pattern that would result in a sum of cubes, a3 b3. his teacher put four products on the board and asked the class to identify which product would result in a sum of cubes if a = 2x and b = y. which product should tomas choose? (2x y)(2x2 2xy – y2) (2x y)(4x2 2xy – y2) (2x y)(4x2 – 2xy y2) (2x y)(2x2 – 2xy y2)
Name the property shown. 4 + 0 = 4 1Commutative Property of Multiplication 2.Identity Property of Addition 3.Commutative Property of Addition 4.Associative Property of Addition
If the base lengths of the prism are doubled, how will the volume be affected?A) it will be multiplied by 2 B) it will be multiplied by 3 C) it will be multiplied by 4 D) it will be multiplied by 6
Find the area if each figure. round the nearest hundredth where neccessary.​

A circular pan has a diameter of 8 inches.What is the exact area of the pan?

A.
256π square inches

B.
8π square inches

C.
64π square inches

D.
16π square inches

Answers

d/2=r
area=pir^2
d=8
8/2=4=r
area=pi4^2
aera=16pi
answer is D

Which angle measure less than or equal to 360° is equivalent to an angle of 17pi/4

Answers

Answer:

Therefore, The required measure of the angle is 45°  

Step-by-step explanation:

\text{The angle is given to be : }(17\pi)/(4)

Now, the value of angle π is equivalent to 180°

So, finding the value of the given angle in degrees

\implies\text{The degree measure of the given angle = }(17)/(4)* 180=765

Now, the angle is 765°

We need to find the angle which measures less than or equal to 360° and is equivalent to 765°

765 = 360 × 2 + 45°

So, 360° angle is 45° less than the given angle.

Therefore, The required measure of the angle is 45°

The correct answer is

45 degrees

:)

A sample with which of these variances has a standard deviation that is greater than the variance?A. 2.25
B. 1.75
C. 0.75
D. 1.25

Answers

By using relation between standard deviation and variance we got that sample with 0.75 variance has a standard deviation that is greater than the variance

What is standard deviation?

Standard deviation is a number used to tell how measurements for a group are spread out from the average (mean), or expected value

Here we have to find a sample with standard deviation greater than the variance.

We know that Standard deviation is the square root of the variance so if we want a sample with greater Standard deviation than the variance  then it's variance  should be less than one as we know that if

0 < x < 1 \Rightarrow \sqrt x > x

And here given variances are

2.25, 1.75,0.75 and 1.25

Hence 0.75 is correct answer

By using relation between standard deviation and variance we got that sample with 0.75 variance has a standard deviation that is greater than the variance

To learn more about standard deviation visit :brainly.com/question/12402189

Standard deviation is the square root of the variance. For the square root of a number to be greater than the number, the number must be between 0 and 1.
Hence, for the standard variation to be greater than the variance, the variance must be between 0 and 1.

Answer: C [0.75]

What is 5/9 equivalent to

Answers

All fractions of form 5k/9k are equivalent to this one, where k is any nonzero integer. Examples: 10/18, 15/27, -5/-9... The decimal form is 0.(5).
5/9 could be equivalent to 10/18, 15/27 or the decimal 0.5(repeating)

What is the equation of a line that goes through the point (4, 2) and is parallel to the line given by the equation y = 2x + 6?y = 4x - 6
y = -2x + 6
y = 2x - 6
y = -2x - 6

Answers

y=2x-6

Parallel lines have equal gradients
Hello,
Answer C

y-2=2(x-4)
==>y=2x-6

Isolate c
a=b(1/c-1/d)

Answers

A= b(1/c - 1/d)
A/b = 1/c -1/d
A/b + 1/d = 1/c
(A/b + 1/d) 1 = c

Answer: c = b/(a + 1).

Step-by-step explanation:

a = b(1/c - 1/d)

Expand RHS by first finding LCM

a = b((d — c)/cd)

a = (bd — bc)/cd

Then cross multiply

acd = bd — cd

Collect the terms having c to the LHS

acd + cd = bd

Factorise cd out of LHS

( a+ 1)dc = bd

c = bd/(a + 1)d

c = b/(a + 1).